Trachoma, an imported disease - Vanista, J; Haicl, P; Benes, C (Central European journal of public health, 1993)
The authors review the incidence of trachoma in the Czech Republic during the last 20 years. Trachoma has become almost exclusively an imported disease. In 1989-1990 the authors treated 34 foreign nationals with imported trachoma at the Infectious Diseases Clinic in Prague. Even after many years' stay in the Czech Republic foreigners may develop exacerbations of the trachomatous process.
Keywords: Afrika; diferenciální diagnóza; Cuba; stupeň závažnosti nemoci; Kuba; Anti-Bacterial Agents; Population Surveillance; Incidence; Jordan; mladiství; Czechoslovakia; Asie; Československo; incidence; Adult; Romové; surveillance populace; Trachoma; Africa; Humans; Jordánsko; trachom; Severity of Illness Index; antibakteriální látky; Asia; Diagnosis, Differential; Roma; dospělí; Adolescent; lidé